Near Infrared Light Triggered Reactive Oxygen Species Responsive Upconversion Nanoplatform for Drug Delivery and Photodynamic Therapy. Issue 8 (17th February 2016) - Zhang, Ting; Lin, Huiming; Cui, Liru; An, Na; Tong, Ruihan; Chen, Yuhua; Yang, Chunyu; Li, Xin; Liu, Jiuyu; Qu, Fengyu
Abstract: Near‐infrared (NIR) light‐sensitive nanocomposites are increasingly receiving attention for their convenient manipulation to obtain on‐demand drug‐release patterns and enhanced therapeutic efficacy. Here, we present a novel strategy based on preparing NaYF4 :Yb, Er@NaYF4 upconverting nanoparticles (UCNP) and coating them with a photosensitizer (chlorin e6; Ce6)‐doped mesoporous silica shell (named UCNP@mSiO2 /Ce6). The thioketal group, a visible light cleavable linker, was chosen as the "gate" to encapsulate the drug (doxorubicin, DOX) in the mesopore by a simple silane coupling reaction. Upon NIR (980 nm) irradiation, the emitted visible light can excite Ce6 to generate reactive oxygen species (ROS) for photodynamic therapy (PDT). In addition, the ROS generation can also break down the thioketal link to induce the "gate" opening and drug release. The in vitro NIR‐triggered release kinetics were investigated by varying the amount of thioketal graft and irradiation intensity. HeLa cells were used as model cancer cells, and detailed cell experiments further illuminate the fast uptake and NIR‐induced cytotoxicity. More importantly, the synergistic action of chemotherapy and PDT led to enhanced cytotoxicity, which means these nanocomposites have potential applications in cancer therapy. Abstract : A drug delivery nanocarrier was constructed with upconverting nanoparticles as the core and photosensitizer‐doped mesoporous silica as the shell. A reactive oxygen species (ROS)‐cleavable thioketal linker was grafted as a "gate" to ensure targeted release. Upon near‐IR irradiation, the visible light emission excites the photosensitizer to generate ROS, which makes the "gate" open and releases the drug.